Transcutaneous ultrasound assessment of internal thoracic artery to coronary artery grafts in patients with and without ischaemic symptoms. Issue 5 (November 1994) - Mauric, A; de Bono, D P; Samani, N J; Spyt, T J; Hartshone, T; Evans, D H
Abstract : OBJECTIVE--To evaluate transcutaneous duplex ultrasound in the assessment of internal thoracic artery to coronary artery grafts. SETTING--Regional cardiothoracic centre. METHODS--Prospective duplex ultrasound evaluation of 83 consecutive patients undergoing left internal thoracic artery to coronary artery grafts, together with combined angiographic and duplex ultrasound evaluation of 17 patients with suspected recurrent myocardial ischaemia after internal thoracic artery grafting. RESULTS--The grafted internal thoracic artery was imaged in 65 (78%) of 83 consecutive postoperative patients, and in 13 (75%) of 17 patients with suspected graft dysfunction. Grafts were recognised by their characteristic position and biphasic blood flow pattern. Resting graft flow was estimated from the time averaged velocity and graft cross sectional area. Median resting flow in patients without ischaemic symptoms was 36 ml/min (interquartile range 24 to 49 ml/min). Of 13 patients with recurrent ischaemia in whom the graft could be imaged, nine patients with estimated flow in the lowest quartile or abnormal flow profiles, or both, had graft disease or anastomotic problems on angiography, while four with satisfactory graft flow on ultrasound examination had normal graft flow on angiography, but had evidence of native disease progression in other vessels. Two of four patients in whom it was not possible to image the graft on ultrasound had satisfactory graft function on angiography. CONCLUSIONS--For those patients whose internal thoracic artery graft can be imaged, transcutaneous duplex ultrasound is a helpful non-invasive guide to graft function. The main limitations to the technique are an inability to image the graft in about 20% of patients, and possible inaccuracy in estimating graft diameter.